Cancer morbidity among workers in the telecommunications industry. Issue 3 (March 1985) - Vågerö, D; Ahlbom, A; Olin, R; Sahlsten, S
Abstract : A retrospective cohort study of 2918 workers in the telecommunications industry in Sweden recorded the cancer morbidity for the period 1958-79. Cases of cancer were collected from the Swedish Cancer Registry for this period and information on work characteristics was collected for the entire period of employment. The total cancer morbidity was as expected. There was no excess risk of lung cancer but an excess risk of malignant melanoma of the skin was detected (SMR = 2.6, 12 cases). This excess risk was particularly associated with work environments where soldering was practised. Estimates of the SMR became larger with the assumption of a longer induction/latency period.